Activated carbon obtained from banana peels for the removal of As (III) from water - Maharjan, Jasana; Jha, Vinay Kumar (Scientific World, 2022)
Present study deals with the preparation of activated carbons from banana peels. The banana peels were subjected to pyrolysis at 700 ℃ for 1 hour in open air (O2-BP), nitrogen gas (N2-BP) and mixture of nitrogen gas and water steam generated to 60-70 ℃ (N2+H2O-BP). The raw and activated carbons from banana peels were characterized by XRD, FTIR and methylene blue adsorption methods.The N2+H2O-BP was used for the adsorption of As (III) ions from aqueous solution. Various parameters affecting the adsorption process like pH (4 to 10), contact time and initial metal ion concentration were varied during the adsorption process. The optimum pH for As (III) adsorption was at 7. An equilibrium time of 2 hours was required for adsorption of As (III) ion. The adsorption isotherms were determined by using Langmuir and Freundlich isotherms and the experimental data were better fitted to Langmuir equation with high coefficient of determination value (R2 = 0.9934). The experimental data fitted well to pseudo second order kinetic model with rate constant value of 0.0111 g/ (mg˖min). The adsorption of As (III) on banana peels was spontaneous and followed physiosorption mechanism. The value of separation parameters (RL) was found to be 0 < RL > 1 for all initial As(III) ion concentrations showed good adsorption of As(III) into banana peels.